Interactive Educational Game Media in Metacognitive Learning to Improve Conceptual Understanding and Science Literacy In Grade V IPA Content in Elementary School - Ni Ketut Fery Nara Andani; I Wayan Wiarta; Didith Pramuditya Ambara (Universitas Pendidikan Ganesha, 2025)
Mathematics learning in elementary schools is still dominated by conventional approaches that lack active and meaningful student engagement, resulting in low conceptual understanding. This study aims to develop and prove the effectiveness of an interactive Student Worksheet (LKPD) based on Project Based Learning (PjBL) to enhance the engagement and learning outcomes of fourth-grade elementary school students. This research is a development study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 25 fourth-grade students. The data collection methods and instruments included interviews, observations, and questionnaires. Data analysis techniques used were descriptive quantitative, qualitative, and inferential analysis. The results showed that the developed interactive LKPD had a very high level of validity and practicality, and it was effective in improving students’ conceptual understanding in mathematics and collaboration skills. The implications of this study indicate that project-based learning media designed according to the characteristics of elementary students can serve as an innovative solution to improve the quality of mathematics learning in a meaningful and enjoyable way.